2011
DOI: 10.1016/j.biortech.2011.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation potential of oily sludge by pure and mixed bacterial cultures

Abstract: The biodegradation capacity of aliphatic and aromatic hydrocarbons of petrochemical oily sludge in liquid medium by a bacterial consortium and five pure bacterial cultures was analyzed. Three bacteria isolated from petrochemical oily sludge, identified as Stenotrophomonas acidaminiphila, Bacillus megaterium and Bacillus cibi, and two bacteria isolated from a soil contaminated by petrochemical waste, identified as Pseudomonas aeruginosa and Bacillus cereus demonstrated efficiency in oily sludge degradation when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
115
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(124 citation statements)
references
References 27 publications
6
115
1
2
Order By: Relevance
“…The employment of mixed bacterial culture has demonstrated to be more advantageous in comparison with pure culture due to synergistic interactions among members of the associations [19]. Due to characteristics of poor nutrients of nitrogen and phosphorus, low BOD/COD ratio, high toxicity, oilfield produced water is difficult to be treated by a simple biological treatment [20].…”
Section: Biological Treatmentmentioning
confidence: 99%
“…The employment of mixed bacterial culture has demonstrated to be more advantageous in comparison with pure culture due to synergistic interactions among members of the associations [19]. Due to characteristics of poor nutrients of nitrogen and phosphorus, low BOD/COD ratio, high toxicity, oilfield produced water is difficult to be treated by a simple biological treatment [20].…”
Section: Biological Treatmentmentioning
confidence: 99%
“…These patterns of TPH degradation were reported by Zucchi et al 2003 andVinas et al 2005 . And similar studies carried out by Cerqueira et al 2011 , demonstrated the degradation of oil sludge by five pure culture isolates viz., Stenotrophomonas acidaminiphila, B. megaterium, B. cereus, B. cibi and Ps. aeruginosa.…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, in the PFR systems, the families Comamonadaceae and Xanthomonadaceae comprised more than 50% of the population, fol- lowed by the Burkholderiaceae family. Members of the Xanthomonadaceae family are obligate aerobes, and some of them have been directly or indirectly related to petroleum hydrocarbon degradation (45,46). The family Comamonadaceae belonging to the order Burkholderiales harbor a remarkable phenotypic diversity, while members of the Burkholderiaceae family from the same order have been found in diverse ecological niches.…”
Section: Discussionmentioning
confidence: 99%